ANALISIS LAPORAN REALISASI ANGGARAN PENDAPATAN DAN BELANJA DAERAH TAHUN ANGGARAN 2019 – 2023 PADA KABUPATEN SEMARANG - Eka Nurlaeli; Candra Sigalingging (Jurnal Studi Akuntansi Pajak Keuangan, 2024)
Benchmarking the progress of the Regional Government in implementing regional development as well as showing regional financial performance seen from the realization of the APBD achieved. The purpose of this research is to describe the financial performance of the Semarang Regency Regional Government during the 2019-2023 period. The research carried out utilized descriptive quantitative methods. The data in this research uses secondary data obtained from the Semarang Regency Regional Government through documentation techniques and literature study. This research resulted in the conclusion that the Semarang Regency Budget Realization Report for the 2019-2023 Fiscal Year was based on an effectiveness ratio of 110.93% or in the very effective category but the efficiency ratio was 99.98% or less efficient. In terms of average income for 2019-2023, it was 101.6% or very effective, average income growth was positive at 1.02% and average expenditure was positive at 5.48%.